Analysis of The Effect of Service Quality on The Level of Satisfaction, Trust and Interest In Revisiting Outpatients At The Hospital dr. Soepraoen Malang - Junaidi, Anang; Siyoto, Sandu; Nurwijayanti, Nurwijayanti (Journal for Research in Public Health, 2019)
The hospital as a health service institution is required to provide a complete service and always maintain the quality of its services. Data on the number of visits of patients in the outpatient poly hospital Dr. Soepraoen Malang in the period of 2016-2017 and in 2018 the number of visits has still not increased and there are still complaints from outpatients on the quality of services provided. This shows that the service has not been optimal. The consumer interest in using the services of the same service provider is strongly influenced by the experience of satisfaction with the services provided previously. Patient satisfaction with hospital services will have an impact on repeat visits and trust in the hospital. The purpose of this study was to analyze the effect of service quality on the level of satisfaction, trust and interest in revisiting outpatients in Dr Soepraoen Hospital Malang. The research design used is quantitative by using analytic surveys. The research design uses Cross Sectional with Accidental Sampling method with a sample of 100 respondents. Data collection using closed questionnaires and interviews. The data analysis used is descriptive analysis, and path analysis. The results showed that the Service Quality variable had a significant effect on the Satisfaction variable; Service Quality variables have a significant effect on the Trust variable; Service Quality variables have a significant effect on the Interest of Revisiting and there is also a joint effect of the variable Quality of Service, Satisfaction, Trust has a significant effect on the Interest in Revisiting Outpatient Hospital Dr. Soepraoen Malang with p-value <0.05. Based on the research, it is necessary to do further research qualitatively about unsatisfactory hospital services.